Demand for online travel sevices in Vietnam / Le Thi Phuong Anh and Ilian Assenov - Anh, Le Thi Phuong; Assenov, Ilian (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2009)
This research presents an overview of the demand by foreign tourists in Vietnam for online travel services, including online searching and purchasing behavior, quality requirements, perception of Vietnamese travel websites, and post- purchase behaviour. Data were collected through questionnaires distributed to international tourists at the end of their stay in Vietnam. The results showed an overall good impression of Vietnamese travel websites. However, Importance- Performance Analysis indicated a number of areas that need improvement. These are discussed in the paper, and recommendations are provided for tourism-related organizations of measures to improve their online offerings use the opportunities presented by the Internet more effectively.